Trade orientation measurement and consequences - Wolf, Holger (Estudios de Economía, 2016)
New trade theory and endogenous growth models have revived the debate on the static and dynamic implications of trade orientation. Alas, a decade of models has produced more ambiguity than clarity, placing a premium on empirical work. Unfortunately, existing indices of trade orientation invite substantial criticism. In the first part of the paper we construct a new measure, based on the difference between actual trade and the trade levels predicted by a factor endowments mode. In the second part, we use the index to examine the link between trade orientation and economic growth.